Порівняльна дія сучасних прокінетиків та нанокристалічного діоксиду церію на моторну функцію травного тракту у щурів різного віку - Єфіменко, Олена; Савченко, Юлія; Фалалєєва, Тетяна; Берегова, Тетяна; Співак, Микола; Iefimenko, Olena; Savchenko, Iuliia; Falalyeyeva, Tetyana; Beregova, Tetyana; Spivak, Mykola (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Встановлено, що нанокристалічний діоксид церію посилював у старих щурів моторну активність шлунка та товстої кишки на відміну від церукалу та сенаде. Нанокристалічний діоксид церію – ефективніший прокі- нетику, ніж сучасні. Отримані результати можуть бути підґрунтям для створення на основі нанокриста- лічногодіоксиду церію протизакрепних засобів нового покоління. In this paper was carried out a comparative study of action of the cerucal, sennosides and NCD on motor function of the stomach and colon in rats. The experiments were performed by ballonographic method.It is shown that cerucal reduces motor, tonic and phasic indexes, amplitude, frequency of the contractions of the stomach and colon in rats. Sennoides increased only the frequency of the contractions, whereas other parameters of motor activity it decreases. It was found that the NCD has stimulated the amplitude, frequency, phase and motor indexes of spontaneous contractile activity of the stomach and colon in rats of both age groups. Thus, the NDC showed effective prokineticffects than current prokinetics. Based on the NCD can be created a prokineticsa new generation.
The Comparative Action of the Modern Prokinetics and Nanocrystalline Cerium Dioxide on the Motor Function of the Digestive Tract in the Rats of Different Ages.
Keywords: нанокристалічний діоксид церію; церукал; сенаде; моторна функція; nanocrystalline cerium dioxide; cerucal; sennosides; motor function